Implementasi Praktik Microteaching dalam Meningkatkan Kompetensi Pengelolaan Pembelajaran Berdiferensiasi Mahasiswa PGSD Unimed - Ivana Silalahi; Shella Yolanda; Rinda Tri Putri; Nurul Aulia; Asna Istikmalatul Muktamaroh (Universitas Negeri Medan, 2026)
The purpose of this study is to investigate how students participate in microteaching techniques as a differentiated learning management strategy in PGSD Unimed. Differentiated learning is a teaching strategy that modifies learning environments, products, processes, and content based on students' learning profiles, interests, and readiness. Observation, interviews, and data analysis were among the descriptive and qualitative techniques used in this study. The results show that students also developed classroom management skills during the microteaching practice. They received training on time management, fostering a supportive learning environment, and developing productive relationships with students, even if it took the shape of a simulation. Students' enthusiasm and learning outcomes are greatly enhanced by diverse learning. Teachers are better able to provide a conducive learning environment when their teaching strategies are adapted to the individual qualities of each student. This makes it easier for students to comprehend the subject matter being taught.